Analysis Of Human Equality In Religious Relations Within Multicultural Society - Julita; A. Suradi; Eza Qurnia Hayati; Eva Puspita Sari; Nursyamsiah (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2025)
This study examines the importance of promoting equality, tolerance, and inclusion in multicultural societies, focusing on the role of religion and the challenges faced in achieving these ideals. Utilizing a qualitative literature review method, the research analyzes secondary sources, including books, scholarly journals, and relevant articles. The findings reveal that discrimination, conflict, and extremism pose significant barriers to equality in diverse contexts. However, principles such as pluralism, tolerance, and interfaith dialogue provide pathways to overcome these challenges. Religion plays a crucial role in shaping societal dynamics through moral values, social structures, and cultural identities. Interfaith dialogue serves as an effective means to foster understanding, build positive relationships, and promote peace among different religious communities. The study emphasizes best practices for fostering inclusion and tolerance, such as inclusive education, open communication, collaboration among faith communities, and a commitment to peace. Ultimately, this research argues that through collective efforts, multicultural societies can develop into inclusive and tolerant environments where individuals coexist peacefully and respectfully, appreciating the richness of diversity.